What determines the exit decision for leveraged buyouts? - Jenkinson, Tim; Sousa, Miguel (Journal of Banking & Finance, 2015)
How and when to exit portfolio company investments are critical choices facing private equity funds. In this paper we analyze 1022 European private equity exits, using information on fund and portfolio company characteristics, and on conditions in capital markets. For over 43% of the exits, private equity funds sold to each other and we analyze why such secondary buyouts have gained in popularity relative to IPOs and sales to corporate acquirers. We find that the exit route depends on various portfolio company characteristics, and that conditions in the debt and equity markets have a strong influence on exit choice. The existing literature has tended to portray the IPO is the “preferred” exit route. However, our analysis suggests this is mistaken: private equity funds take advantage of ‘windows of opportunity’, and the exit route that maximizes value varies with market conditions.